Impact of Hepatic Arterial Anomalies on Postoperative Outcomes following Pancreaticoduodenectomy: A Retrospective Case-control Analysis - Puvvada Prashanth; Sankareswaran Sugaprakash; Raju Prabhakaran; Chidambaranathan Sugumar (Journal of Clinical and Diagnostic Research, 2025)
Introduction: Arterial anomalies are frequent occurrences and pose challenges during major surgeries like Pancreaticoduodenectomy (PD), especially during gastroduodenal artery ligation and lymph node dissection. Aim: To analyse the influence of arterial anomalies on mortality and morbidity, as well as oncological adequacy in terms of R0 rate and lymph node retrieval. Materials and Methods: A The present retrospective analysis included a total of 25 patients with vascular anomalies reported on Computed Tomography (CT) angiography who underwent PD over a period of four years (January 2020-December 2023) and were compared with 25 patients without vascular anomalies. This analysis was conducted from January 2024 to March 2024. Intraoperative events such as blood loss, blood transfusion requirements and operative time were compared between both the groups. Postoperative complications, including pancreatic leak, Hepaticojejunostomy (HJ) leak, delayed gastric emptying, postpancreatectomy haemorrhage, relaparotomy and mortality, were also compared. Fisher’s two-tailed exact test, t-test and Chi-square tests were employed, with p-value<0.05 considered significant. Results: The two groups were evenly matched regarding patient demographics. The most common variation was the Replaced Right Hepatic Artery (RRHA) (48%) arising from the Superior Mesenteric Artery (SMA), followed by the Replaced Common Hepatic Artery (CHA) (20%) arising from the SMA. There was no significant difference (p-value>0.05) in blood loss, the need for blood transfusion, or operative time. Postoperative morbidity due to pancreatic leak, bile leak, postoperative haemorrhage, relaparotomy rate and 30-day mortality was also not significantly different. There was no difference in resection margins (R0) and lymph node yield (10 vs 11) between the two groups. Conclusion: Aberrant hepatic arteries do not significantly increase morbidity or compromise oncological safety in patients undergoing PD by experienced surgeons.